Multiple paralogues of α-SNAP in Giardia lamblia exhibit independent subcellular localization and redistribution during encystation and stress - Shankari Prasad Datta (Parasites & Vectors, 2018)
Abstract Background The differently-diverged parasitic protist Giardia lamblia is known to have minimal machinery for vesicular transport. Yet, it has three paralogues of SNAP, a crucial component that together with NSF brings about disassembly of the cis-SNARE complex formed following vesicle fusion to target membranes. Given that most opisthokont hosts of this gut parasite express only one α-SNAP, this study was undertaken to determine whether these giardial SNAP proteins have undergone functional divergence. Results All three SNAP paralogues are expressed in trophozoites, encysting trophozoites and cysts. Even though one of them clusters with γ-SNAP sequences in a phylogenetic tree, functional complementation analysis in yeast indicates that all the three proteins are functionally orthologous to α-SNAP. Localization studies showed a mostly non-overlapping distribution of these α-SNAPs in trophozoites, encysting cells and cysts. In addition, two of the paralogues exhibit substantial subcellular redistribution during encystation, which was also seen following exposure to oxidative stress. However, the expression of the three genes remained unchanged during this redistribution process. There is also a difference in the affinity of each of these α-SNAP paralogues for GlNSF. Conclusions None of the genes encoding the three α-SNAPs are pseudogenes and the encoded proteins are likely to discharge non-redundant functions in the different morphological states of G. lamblia. Based on the difference in the interaction of individual α-SNAPs with GlNSF and their non-overlapping pattern of subcellular redistribution during encystation and under stress conditions, it may be concluded that the three giardial α-SNAP paralogues have undergone functional divergence. Presence of one of the giardial α-SNAPs at the PDRs of flagella, where neither GlNSF nor any of the SNAREs localize, indicates that this α-SNAP discharges a SNARE-independent role in this gut pathogen.